Lughoh Science In the Modern Era: Arabic Language From Rules to Reality - Hidayatullah, Muh Arya Satya; Azzahra, Salwa; Waluyo, Azriel Shabrina Djenar (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This is a study on linguistic development and how modern Arabic grammar influences the knowledge and application of the Arabic language. Arabic is one of the languages with a long history and a rich structure of rules. Arabic is used in various contexts due to technological advancements, globalization, and digital media. This discusses how Arabic has evolved from classical rules to modern usage, including the emergence of new words, the decline of grammatical structures, and the phenomenon of Arabic in everyday communication. Additionally, this paper emphasizes the challenges faced in maintaining the authenticity and integrity of the language, as well as the role of technology such as artificial intelligence and Google Translate in the translation and education of Arabic. Using a descriptive-analytical approach, the aim of this paper is to gain a better understanding of the current dynamics of the Arabic language and the impact it has on learning and communication worldwide.